An examination of individual forms of nonsuicidal self-injury. (August 2019) - Ammmerman, Brooke A.; Hong, Max; Sorgi, Kristen; Park, Yeonsoo; Jacobucci, Ross; McCloskey, Michael S.
Highlights: There is a need to identify indicators of severe NSSI behavior. Limited research has examined individual NSSI methods. NSSI method of self-hitting / punching emerged as important in negative outcomes. Self-cutting may also confer risk for severity. Abstract: Nonsuicidal self-injury (NSSI) is a growing public health concern, and there is an increasing need to better characterize and identify severe NSSI behavior. One readily accessible, yet understudied, avenue for improving the assessment of NSSI severity is through the examination of individual forms, or methods, of the behavior. The present study aimed to address this gap in the literature by investigating the relationship between 12 different NSSI methods with three NSSI severity indicators and three distinct suicidal thoughts and behaviors among 1, 436 undergraduate students with a history of NSSI (70.90% female, M age = 20.69, SD  = 3.32). Results across six decision tree analyses highlighted the use self-hitting / punching, in addition to cutting oneself, as the most informative NSSI methods for differentiating outcome severity. Gender differences were only found for the outcome of suicidal ideation. The present study provides preliminary evidence that the examination of individual NSSI methods may be useful in identifying individuals at risk for negative correlates of NSSI, including NSSI-related hospital visits, unintended serious injury, and suicidal behavior. Upon replication in longitudinal work, findings have important clinical utility by providing a potential marker of prognosis and the need for higher levels of care.